Polysemy in Context - Movsisyan, Diana (Armenian Folia Anglistika, 2012)
The current article studies the contextual manifestation of polysemy, the influence of the context on the formation and perception of the meaning of the word. The word light in the short story The Apple Tree by John Goldsworthy has been analyzed to demonstrate the possible semantic shades it can obtain in the context.